Letter (copy) - Tewson, Vincent
026-0087-001 Secretary's. HVT/FC/508. 26th May, 1939. Senor Pablo Alvaro, Girton House, Kingsway, Hove, SUSSEX. Dear Senor Alvaro, I am sorry for the delay in sending the parcel of clothing referred to in my letter of the 16th May, but we are despatching it to-day and hope it will be of some little help to your colleagues. Yours sincerely, Assistant Secretary 292/946/26/87